Papillary neoplasms of biliary tract-a histopathological surprise - P. S., Sreejith; Urabinahatti, Kiran; A., Arunkumar; Amudhan, A.; S., Jeswanth (International Surgery Journal, 2023)
Papillary neoplasms of the biliary tract is a relatively new entity which most often comes as a histological surprise. They are often diagnosed as malignancies and are treated like that. But the prognosis is better when compared to malignancy itself. Here we reported two cases of papillary neoplasms of the biliary tract. First case was a 50 year old male who was evaluated for obstructive jaundice and on evaluation found to be type 3b hilar cholangiocarcinoma and underwent left hepatectomy with extra hepatic bile duct resection and portal lymphadenectomy. Histo-pathological report was intra-ductal papillary neoplasm - biliary type (IPN B). Second case was an incidental finding of arterial enhancing lesion in the gallbladder wall on CT scan, which was done for the evaluation of bicytopenia. This also was reported as malignancybin pre-operative imaging and hence underwent anticipated extended cholecystectomy with wedge resection of 2 cm adjacent hepatic parenchyma. Again histopathology revealed it as intra-cholecystic papillary neoplasm with focal dysplasia. Both cases were followed up for more than one and half years and showed no evidence of recurrence, hence pointing towards better prognosis. Papillary neoplasms are difficult to diagnose preoperatively and are often treated with oncological resections but they carry a better prognosis when compared with their malignancy counterparts.